Extending the limits of Higgs effective theory - Biekötter, Anke; Brehmer, Johann; Plehn, Tilman (Physical review, 2016)
Based on a vector triplet model, we study a possible failure of dimension-6 operators in describing LHC Higgs kinematics. First, we illustrate that including dimension-6 contributions squared can significantly improve the agreement between the full model and the dimension-6 approximation, both in associated Higgs production and in weak-boson-fusion Higgs production. Second, we test how a simplified model with an additional heavy scalar could improve the agreement in critical LHC observables. In weak boson fusion, we find an improvement for virtuality related observables at large energies, but at the cost of sizeable deviations in interference patterns and angular correlations.